Pengaruh Perbandingan Batang Sawit dalam Pembuatan Pupuk Kompos - Nina Veronika (Jurnal Sains dan Ilmu Terapan, 2021)
The utilization of palm trunks has not been optimal and was a problem for oil palm plantation rejuvenation because of its huge amount, reaching 220 m3 / hectare. And it was a method to utilize waste trunks into products that are worth selling, environmentally friendly and give benefits for oil palm growers. In particularly, the target of this research was a product in the form of compost fertilizer made from raw waste palm trunks. The high nutrient resources owned by palm trunks were expected to produce high quality compost. Based on the result of the research of composting of palm trunks and the analysis of each of the above compost which include the level of C / N, C - Organic, N, P, K, pH and water ratio, it could be concluded that good compost type was found in variable compost 4 which with the result of C / N ratio 18,9%, C - Orgaik 21,5%, value of N, P, K approaching 4 that is 3,97%, pH 8,43% and water content 24%.